Mitochondrial phenotypes in iPSC AD models. (31st December 2021) - Flannagan, Kaitlin; Stopperan, Julia A.; Troutwine, Benjamin M; Lysaker, Colton R; Strope, Taylor; Draper, Julia; Shaddy‐Gouvion, Cynthia; Vivian, Jay; Haeri, Mohammad; Wilkins, Heather M
Abstract: Background: Mitochondrial dysfunction is observed in Alzheimer's disease (AD). Altered mitochondrial respiration, cytochrome oxidase (COX) Vmax, and mitophagy are observed in human subjects and animal models of AD. Models derived from induced pluripotent stem cells (iPSCs) may not recapitulate these phenotypes after reprogramming from differentiated adult cells. We examined mitochondrial function across iPSC derived models including cerebral organoids, forebrain neurons, and astrocytes. Postmortem brain tissue was used as a comparison. Method: iPSCs were reprogrammed from fibroblasts either from the University of Kansas Alzheimer's Disease Research Center (KU ADRC) cohort or purchased from WiCell. Postmortem brain samples were from the KU ADRC cohort when available. A total of four non‐demented and four sporadic AD iPSC lines were examined. Postmortem brain tissue was derived from 9 ND and 12 AD subjects. iPSCs were differentiated into neurons, astrocytes, or cerebral organoids using StemCell Technologies protocols and reagents. iPSC derived models and postmortem brain tissue were subjected to mitochondrial respiration analysis using Seahorse XF technology and spectrophotometric COX Vmax assays. iPSC derived neurons and astrocytes underwent fluorescent assays to determine mitochondrial mass, mitochondrial membrane potential, and mitophagy levels. Result: iPSC derived neurons and cerebral organoids showed reduced COX Vmax in AD subjects. These results were not observed in astrocytes. Postmortem human brain samples showed reduced COX Vmax in AD subjects. iPSC derived neurons had reduced mitochondrial respiration parameters, mitochondrial mass, mitophagy, mitochondrial membrane potential, and mitochondrial superoxide production. iPSC derived astrocytes had reduced mitochondrial respiration parameters but increased mitochondrial membrane potential and no change in mitochondrial superoxide production. Conclusion: iPSC derived models from AD subjects show mitochondrial dysfunction phenotypes like what is observed in postmortem brain. As iPSCs do not maintain their epigenetic signatures after reprogramming the observed phenotypes are likely due to other somatic factors.